Feasibility of shared use of alternative AC diesel generator under dual-unit station blackout. Issue 10 (3rd October 2017) - Kim, Man Cheol
ABSTRACT: The Fukushima accident raised concerns about the preparation level of nuclear power plants against multi-unit accidents. Under dual-unit station blackout (SBO), it is generally considered that the alternate AC diesel generator (AAC DG) is connected to only one unit, and core damage is inevitable in the other unit. Based on the lessons from Fukushima Daiichi Units 5 and 6, which successfully mitigated the situation by sharing one emergency diesel generator, this study investigates the feasibility of shared use of the AAC DG under a dual-unit SBO. A thermal-hydraulic (TH) code analysis with conservative assumptions demonstrated that both units are able to withstand and recover from dual-unit SBO by the shared use of the AAC DG. The review of the TH code analysis results by changing the conservative assumptions to more realistic assumptions also provide strong support for the same conclusion. After being properly incorporated into operational procedures, such as emergency operating procedures, the shared use of the AAC DG under a dual-unit SBO is expected to significantly reduce plant risk.